Integration in the global sourcing organization–an information processing perspective - Trautmann, Gerhard; Turkulainen, Virpi; Hartmann, Evi; Bals, Lydia (Journal of Supply Chain Management, 2009)
Global sourcing refers to the integration of decision making across worldwide purchasing units within a multinational corporation (MNC). In order to manage the integration challenge, firms have a number of tools, varying from centralization and formalization to cross-locational teams. In this paper, we focus on explaining how and why to integrate in different circumstances. The aim of this paper is to complement prior research on global sourcing organizations, which is still rather scarce and more exploratory in nature. By extending the arguments of the information processing perspective of organizations to the global sourcing context, we seek to propel a theoretical discussion on integration in the global sourcing organization. Based on the results of 12 case studies in three MNCs, we propose that integration approaches in global sourcing organizations vary depending on the three contingencies of category characteristics, supply environment characteristics and interdependence of the purchasing units.
WiSo-Import:2015-03-26:1019
Keywords: organization; international/global purchasing; case studies; Innovation